Consumer Legal Protection in the Digital Era: Indonesia and The European Union - Mau, Hedwig Adianto (Faculty of Law, Universitas Pattimura, 2025)
Introduction: This study compares consumer protection laws in the digital era in Indonesia and the European Union (EU).Purposes of the Research: The study is grounded in consumer protection theory, focusing on the legal principles governing consumer rights, data privacy, and dispute resolution in digital transactions.Methods of the Research: A qualitative comparative approach was employed, analyzing primary legal texts such as Indonesia's Consumer Protection Law and the Personal Data Protection Law, the EU's General Data Protection Regulation (GDPR), and relevant consumer protection directives.Results of the Research: The analysis demonstrates a significant contrast between the two jurisdictions. The European Union has established a highly developed and harmonized legal framework—most notably through the GDPR—which ensures consistent protection of consumer data across its member states. By contrast, Indonesia’s legal framework, although supported by the Consumer Protection Law and the Personal Data Protection Law, remains fragmented and continues to encounter challenges in enforcement as well as inter-agency coordination. Whereas the EU adopts a preventive and rights-based regulatory approach designed to safeguard consumers proactively, Indonesia’s model tends to be more reactive, relying on sectoral regulations and post-violation enforcement mechanisms. These findings underscore the necessity for Indonesia to strengthen enforcement capacity, enhance regulatory harmonization, and adopt a more comprehensive approach capable of addressing the rapid expansion of digital commerce.